Assessment of effectivity and adaptability of DOAP as a teaching and learning method by II-MBBS students for intravenous cannulation in simulated environment - Dhavalshankh, Archana Ganesh; Dhavalshankh, Ganesh P.; Dhavalshankh, Gayatri Ganesh (International Journal Of Community Medicine And Public Health, 2024)
Background: Before implementing any teaching and learning method in the curriculum, it is required to evaluate its effectivity, feasibility and adaptability. DOAP is one new TL method in CBME help to facilitate self-directed, long-term learning and to cultivate and enhance interest in the study. This study aimed to assess the effectivity and Adaptability of DOAP as a teaching and learning method by II-MBBS students for intravenous cannulation in simulated environment. Methods: For this cross-sectional, data collected from 150 students from MBBS II phase. Demonstration by a trained facilitator for a group of 10 followed by assistance and then performance by individual student under supervision using mannequin in simulated environment. The effectivity assessed with knowledge domain using pre-test and post-test and skill domain, OSPE checklist validated by subject expert used. Adaptability assessed after feedback from students and teachers. Statistical analysis was done using t test. Results: There was graded improvement seen after post-test I and II (44.62% and 70.08% respectively). The significant improvement was seen in performance with pre and post OSPE mean score results (11.74, 16.48 and 19.6 respectively) with p value less than 0.001 after both post DOAP OSPE. As per students’ and teachers’ feedback DOAP is very much effective TL method to impart knowledge, skill and communication domain on IMG. Conclusions: DOAP is effective TL method to impart knowledge, skill and communication domain on IMG. Pre-requisites like infrastructure, trained facilitators and time constraints has to consider before its implementation.